2017
DOI: 10.18203/2320-1770.ijrcog20170551
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D in pregnancy and its correlation with preeclampsia and gestational diabetes mellitus

Abstract: Background: Hypovitaminosis D has been associated with a number of adverse pregnancy outcomes, and has been recognised as a public health concern. The objective of this study was to determine the impact of Vitamin D deficiency on maternal complications like gestational diabetes mellitus (GDM) and preeclampsia (PE) among pregnant women.Methods: This was a case control study undertaken at antenatal clinics and indoor of BRD Medical College, Gorakhpur, Uttar Pradesh, India. Two maternal blood samples, one at <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…(2019), 23 Choudhary N et al (2018), 24 Sahu M et al (2017), 13 Baror S et al (2017), 16 Kumari A et al (2017), 25 Goel P et al (2016), 14 Sadin B et al (2015), 21 Singla et al (2015) 26 and Bakacak et al (2015). 15 Our study also demonstrated that though vitamin D deficiency was common in all antenatal patients but it was significantly more prevalent in preeclamptic women.…”
Section: Variablementioning
confidence: 99%
“…(2019), 23 Choudhary N et al (2018), 24 Sahu M et al (2017), 13 Baror S et al (2017), 16 Kumari A et al (2017), 25 Goel P et al (2016), 14 Sadin B et al (2015), 21 Singla et al (2015) 26 and Bakacak et al (2015). 15 Our study also demonstrated that though vitamin D deficiency was common in all antenatal patients but it was significantly more prevalent in preeclamptic women.…”
Section: Variablementioning
confidence: 99%